KINERJA REKSA DANA DI INDONESIA DITINJAU DARI PEMILIHAN SAHAM, DAN TINGKAT RISIKO - Diyan Lestari (Universitas Ahmad Dahlan, 2019)
Mutual fund is a pool investment which combines many investment products. It is managed by investment manager. It can be stock, bond, and other investment products. Currently, there is positve trend of mutual fund performance in Indonesia. It can be concluded that Indonesian tend to realize the positive impact of mutual fund investment which has relatively fix returns compare to other investment products. However, the stability of economic and political condition in Indonesia also drive the positive trend of mutual fund investment. Every investors want to gain optimal return. They will observe the mutual fund which has the maximum return. To predict mutual fund performance, many studies consider threee measurement which is Sharpe, Tryenor amd Jensen. This study aims to examine the mutual fund performace based on stock selection, and risk consideration.. This study use pool regression to analyze the data. The result shows that risk level do not effect the mutual fund performance, while stock selection effect the mutual fund performance.